Interactions à distance synchrones entre apprenants de FLELe clavardage au service du français académique - Hyeon Yun; Françoise Demaizière (Recherches en didactique des langues et des cultures)
Computer Mediated Communication (CMC) is a challenge for language teaching and learning research as well as an opportunity to create new language learning situations. The potential of synchronous written CMC chat is studied here. Chat sessions were organized for advanced level foreign students (Masters, PhD) and researchers enrolled in a French university. These students need to master French as it is used in an academic setting (doctoral presentations, seminars, etc.). This article analyzes the structure of the learners' utterances, their use of lexical items, of complex structures and the influence of their other languages on their productions in French from an interactional and acquisitional perspective.